Clinical presentation and neurovascular manifestations of cardiac myxomas and papillary fibroelastomas: a retrospective single-institution cohort study - Mathavan, Akshay; Mathavan, Akash; Krekora, Urszula; Mathavan, Mohit; Rodriguez, Vanessa; Altshuler, Ellery; Nguyen, Brianna; Ruzieh, Mohammed (Frontiers in Cardiovascular Medicine, 2023)
Background Primary cardiac tumors are often benign and commonly present as cardiac myxomas (CMs) or papillary fibroelastomas (CPFEs). There is a paucity of prognostic indicators for tumor burden or potential for embolic cerebrovascular events (CVEs). This study was performed to address these gaps. Methods Medical records at the University of Florida Health Shands Hospital between 1996 and 2021 were screened to identify patients with CMs or CPFEs. Clinical features, echocardiographic reports, and CVE outcomes were quantitatively assessed. Results A total of 55 patients were included in the study: 28 CM (50.9%) and 27 CPFE (49.1%) patients. Baseline patient characteristics were similar among patients. The neutrophil–lymphocyte ratio was correlated (p < 0.005 in all cases) to three metrics of tumor size in both CM (r = 64–67%) and CPFE (r = 56–59%). CVEs were the presenting symptom in 30 (54.5%) patients. CVE recurrence was high; the 5-year CVE recurrence rate in patients with tumor resection was 24.0% compared to 60.0% without resection. No baseline patient characteristics or tumor features were associated with an initial presentation of CVEs compared to any other indication. Univariate analysis indicated that prolonged duration to surgical resection, left atrial enlargement, male sex, and a neutrophil–lymphocyte ratio >3.0 at the follow-up were significantly associated with 5-year CVE recurrence. Left atrial enlargement and a neutrophil–lymphocyte ratio >3.0 at the follow-up remained significantly associated with 5-year CVE recurrence in multivariate analysis. Conclusion The neutrophil–lymphocyte ratio may prognosticate tumor size and recurrence of neurologic events. An increased risk of CVE within 5 years of mass resection is almost exclusive to patients initially presenting with CVEs.